The selective antagonism of bradykinin action on rat isolated uterus by crude Mandevilla velutina extract. - Calixto, J. B. (1985)
A crude aqueous alcoholic extract of Mandevilla velutina (Apocynaceae) rhizomes produced a concentration-dependent displacement to the right of the concentration-response curve to bradykinin (Bk) in the isolated uterus of the rat. Schild analysis of the data revealed a linear relationship (r = 0.99) and yielded a pA2 value of 3.3 + 0.08 (- log g ml-1) but the slope differed significantly from unity. The anti-Bk action was of rapid onset and was reversible upon washout. Contractions induced by acetylcholine, oxytocin, angiotensin II and BaCl2 were unaffected by the extract. This represents the first report of a selective Bk antagonist of plant origin. The isolation of the active principle(s) may result in a useful pharmacological tool for elucidating the physiological and physiopathological roles of endogenous Bk.